Odpowiedzi

Najlepsza Odpowiedź!
2009-12-17T23:19:32+01:00
(a) -x/2= 3x- 3+2x/4 MNOŻE OBUSTRONNIE PRZEZ 2
-x = 6x - 6 + 4x/4
-x = 6x-6 + x
-x = 7x - 6
-x - 7x = -6
-8x = -6
x = 3/4
x = 0,75


(b) 3-3x/2=5/8-4x-3/6 odejmuje 3
-3x/2 = 5/8 - 4x-3/6 - 3 mnoże przez 2
-3x = 10/8 - 4x-3/3 - 6
-3x + 4x-3/3 = 10/8 - 6
-3x + 4/3 x - 1 = 10/8 - 6
-5/3 x = 10/8 - 6 +1
- 5/3 x = -3,75
x = 2,25

2009-12-17T23:25:58+01:00
A) -x/2= 3x- 3+ 2x/4 (*2)
-x = 6x - 6 + x
8x = 6
x = 6/8 = 3/4

b) 3 - 3x/2 = 5/8 - 4x - 3/6 (*2)
6 - 3x = 5/4 - 8x -1
5x = 1/4 - 24/4
5x = -23/4
x = -23/20